Explanatory Case Study on the Implementation of Quantum Communication Protocols in Enhancing the Security of Industrial Internet of Things Networks - Sawitri, Dara (Politeknik Negeri Lhokseumawe, 2025)
The Internet of Things (IoT) continues to face fundamental challenges in communication security, primarily due to the limited resources of devices and their highly distributed nature. The integration of quantum communication is considered a strategic breakthrough to strengthen data protection through encryption mechanisms based on quantum principles. This research is directed toward analyzing the implementation and adaptation of quantum communication protocols within industrial IoT ecosystems, with the aim of enhancing the security of data exchange. The findings indicate that the success of implementation is strongly influenced by two major factors: the technical compatibility of devices and the management of organizational aspects, including cross-unit coordination and resistance to change. The novelty of this study lies in its focus on real-world implementation of quantum communication protocols in industrial environments, which have previously been examined predominantly through theoretical or simulation-based approaches. By integrating both technical and managerial dimensions, this research contributes to a comprehensive understanding of adaptation mechanisms for quantum protocols while providing practical recommendations for the development of more applicable and sustainable communication security strategies.